STUDI KOMPARATIF PERILAKU PENCEGAHAN DEMAM BERDARAH DENGUE DI DAERAH URBAN DAN RURAL (Studi pada Wilayah Kerja Puskesmas Karanglewas) - Maqfiroch, Arrum Firda Ayu (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2019)
Background : Dengue Hemorrhagic Fever (DHF) is one of the public health problem that caused by Dengue virus. The preventive behavior towards DHF disease performed by rural and urban society suited to the infecting agent vector and the different characteristic of urban and rural society. This research aimed to analyse the different preventive behavior towards DHF performed by the urban and rural society. Methods : This research is a quantitative research by Cross Sectional approach. The population of the research are 15.943 households in Puskesmas Karanglewas working area with the sample taken from households in chosen 7 villages by using Cluster Random Sampling with 97 respondents in urban area and rural area. The data collection technique was carried out by using questionnaire and observation. Then the data analyses are univariate, bivariate and multivariate.  Results : the variable that has no difference were the availability of medium and infrastructure (p=0,953) and the role of health officer (p=0,088). Besides, the different variables were the level of education (p=0,001), income (p=0,000), knowledge (p=0,000), behavior (p=0,000), exposure of information (p=0,000), the role of social figure (p=0,000), and the preventive behavior (p=0,000). Conclusion : The different variables between the urban and the rural society are the level of education, income, knowledge, behavior, the exposure of information, the role of social figure, and the preventive behavior towards the DHF.